2005
DOI: 10.1007/s10533-004-0362-0
|View full text |Cite
|
Sign up to set email alerts
|

The High Arctic glacial ecosystem: new insights from nutrient budgets

Abstract: Abstract. This paper describes detailed budgets of water, Cl ) , dissolved Si and both inorganic and organic forms of nitrogen and phosphorus for two small glacier basins in Arctic Svalbard (Midre Love´nbreen and AustreBrøggerbreen). Rates of nutrient deposition are modest, dominated by inorganic nitrogen and episodically enhanced by extreme events. Hence deposition rates are also variable, ranging from 20 to 72 kg NO 3 -N km )2 a )1 and 10-37 kg NH 4 -N km )2 a )1 over just two consecutive years. Deposition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
236
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(256 citation statements)
references
References 34 publications
15
236
2
Order By: Relevance
“…This model has previously been used in a snowmelt study at this site and is described by Hodson et al (2005). It uses radiation, humidity, and temperature data from Ny-Ålesund that was provided by the Alfred Wegener Institute (AWI) through S. Debatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model has previously been used in a snowmelt study at this site and is described by Hodson et al (2005). It uses radiation, humidity, and temperature data from Ny-Ålesund that was provided by the Alfred Wegener Institute (AWI) through S. Debatin.…”
Section: Discussionmentioning
confidence: 99%
“…If particles and bacteria remain in the snowpack rather than following the meltwater, as our results suggest, an elevated concentration of associated chemicals (such as NO 3 -) might be expected in the remaining snow. This is because both nitrification, which is typical among bacteria associated with debris (Hodson et al, 2005), and cell-lysis, which may be caused by osmotic stress in the very diluted meltwater (Harding et al, 2011), might release solutes to the surrounding snow and meltwater. Furthermore, chemical dry deposition and sublimation of snow-water could also influence the snowpack concentrations and thereby the elution response.…”
Section: Ion Elutionmentioning
confidence: 99%
“…No data are available for the snowpack at Site 1, but analyses of snow on nearby glaciers found that concentrations of DON were generally less than those of inorganic N (Hodson et al 2005). In contrast, and in common with many low N systems, concentrations of DON in the stream generally exceeded those for total inorganic N (Table 2b).…”
Section: Organic Nitrogenmentioning
confidence: 99%
“…focused on glacial catchments Wadham et al 2004;Hodson et al 2005;Wynn et al 2006). These systems have major roles in (i) regulating the biogeochemical cycling of nutrients that may impact both freshwater and marine ecosystems and (ii) in our understanding of cryosphere-atmosphere interactions and the potential feedbacks that contribute to climate regulation .…”
Section: Studies Of Chemical Budgets and Hydrochemistry In The Europementioning
confidence: 99%
See 1 more Smart Citation